2004
DOI: 10.1159/000077586
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Maternal Body Composition and Birth Weight

Abstract: In order to establish the relationship between maternal body composition indicators (fat-free mass, fat mass, total body water) and birth weight, a cross-sectional study was designed, based on 196 pairs of mothers and live singleton newborns with gestational age of 37 weeks or more. Immediately after delivery, the mothers were interviewed to obtain information about different birth weight predictors. An analysis of maternal body composition through bioelectric impedance was held. Multiple linear regression was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
1
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 22 publications
(34 reference statements)
3
41
1
5
Order By: Relevance
“…These results are in accordance with previous studies where maternal FFM was found to be positively related to infant birth weight (91)(92)(93). The findings in this thesis contribute additional knowledge, since it was demonstrated that it was the FFM of infants, rather than the FM, that is related to maternal FFM.…”
Section: Parental Body Composition Versus Infant Size and Body Compossupporting
confidence: 92%
See 1 more Smart Citation
“…These results are in accordance with previous studies where maternal FFM was found to be positively related to infant birth weight (91)(92)(93). The findings in this thesis contribute additional knowledge, since it was demonstrated that it was the FFM of infants, rather than the FM, that is related to maternal FFM.…”
Section: Parental Body Composition Versus Infant Size and Body Compossupporting
confidence: 92%
“…The findings in this thesis contribute additional knowledge, since it was demonstrated that it was the FFM of infants, rather than the FM, that is related to maternal FFM. Given the present results, it is possible that the reported positive association between maternal BMI and infant birth weight (91)(92)(93) may to a large extent be due to an effect of the FFM rather than the FM of the mother. Further, Starling et al found that maternal BMI was associated with both infant FM and FFM (19).…”
Section: Parental Body Composition Versus Infant Size and Body Composmentioning
confidence: 66%
“…Some authors try to close this gap by deriving their own reference values [3] , but do not use different test and training datasets, which biases results. In addition, maternal height and weight should be considered when defining growth retardation in the offspring [13,14] .…”
Section: Discussionmentioning
confidence: 99%
“…However, associations persist in studies that have used net gestational weight gain (i.e. birth weight subtracted from total weight gain) as an exposure [76] . In addition, it is possible that shared genes underlie greater maternal and fetal weight gain.…”
Section: Gestational Weight Gain and Infant Health Fetal Growthmentioning
confidence: 99%